2018
DOI: 10.1007/s00168-018-0892-3
|View full text |Cite
|
Sign up to set email alerts
|

Regional preferences for the living environment and mobility of researchers and general workers: the case of Korea

Abstract: Since 2005, the Korean government has relocated national research institutes from the Seoul Metropolitan Area (SMA) to other parts of the nation. The main purpose of this relocation is to ameliorate disparities in population and economic power across regions. However, it turns out that only 27% of researchers in the SMA have actually relocated. This implies that researcher's preference for a living environment should be reflected in the planning process. Hence, this paper attempts to specify the migration beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 46 publications
2
5
0
Order By: Relevance
“…A high-quality living environment can attract more knowledge workers, which is the driving force for knowledge and innovation. [22,77]. The results of this research also showed that lifestyle convenience is positively correlated with the agglomeration of high-tech firms.…”
Section: The Effects Of Built Environment On the Location Choice And supporting
confidence: 55%
“…A high-quality living environment can attract more knowledge workers, which is the driving force for knowledge and innovation. [22,77]. The results of this research also showed that lifestyle convenience is positively correlated with the agglomeration of high-tech firms.…”
Section: The Effects Of Built Environment On the Location Choice And supporting
confidence: 55%
“…Kofler et al (2020) present survey results that high-skilled workers particularly want a multicultural and tolerant environment, research and educational institutions, good traffic connections, healthcare facilities, and childcare facilities. Lee and Kim (2019) confirm the finding that living environment as measured by crime rates, annual visitors to cultural and leisure facilities, and green areas per person is especially attractive to high-skilled workers in Korea, while Le Gallo and Plunket (2020) focus on networks headed by "gatekeepers"highly skilled individuals who help coordinate local linkages between highly skilled workers. Finally, Hu and Zheng (2020) highlight how different governments pursue different approaches, often with similar results.…”
Section: Local Amenitiessupporting
confidence: 54%
“…Furthermore, the mobility of high-skilled labor is greater (Davis & Dingel, 2019). Therefore, human capital in neighboring cities will migrate to areas with more developed industrial intelligence, resulting in brain drain (Lee & Kim, 2018), which inhibits inclusive green growth in neighboring cities.…”
Section: Policy Effect Analysismentioning
confidence: 99%